Sustainable tourism opportunities for Mauritius - Ternel, Maeva (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
Sustainable Tourism (ST) integrates governance, economic, socio-cultural and environmental dimensions of tourism in tourism development and management. Growing Environmental, Social and Governance (ESG) concerns suggest that traditionally, tourism tends to corrupt the very resources it needs to thrive, and thus its sustainability over the long haul has become of general concern. However, despite the vast and extensive literature dedicated to ST, including preeminent journals providing both a theoretical base and reliable empirical evidence to the subject, the concept of sustainability in tourism remains somehow at its embryonic stage, especially in the case of a small island developing state (SIDS). The research occurred within the context of the destination (Mauritius), with however, a focus on five sizeable Mauritian hotel groups. With tourism being one of the pillars of the Mauritian economy, this research intended to explore the different repercussions of such an industry. The aim of the research was to determine to what extent tourism's operations and development, was appropriately managed in Mauritius by assessing the country's current tourism situation relating to sustainability and identifying priority areas for intervention. This, was done using different tools, including the United Nations World Tourism Organisation's framework, the Global Sustainable Tourism Council's guidelines and the Sustainable Tourism Attitude Scale. The contribution this research intended to make was to suggest sustainable tourism opportunities and make recommendations for the tourism sector and its stakeholders for the island of Mauritius. Overall, the research concluded that despite the increased importance of ST, the need for Managed Tourism (MT) and the formulation of general principles and guidelines, tourism governance; poverty reduction; and the sustainability of the natural and cultural environment were identified as areas of particular need and should be considered with high priority for intervention/action.
Keywords: Uncatalogued